Djibouti Looks to the Future : A South-South High Level Exchange - Fotouhi, Homa-Zahra; Foch, Arthur; Vakil, Roya (2014)
This quick note highlights the key discussions and recommendations made during the high-level development exchange held in Djibouti on June 20-23, 2014. The event was co-organized by the World Bank office in Djibouti and the ministry of economy and finance under the high patronage of the President of the Republic of Djibouti. The event provided a platform to promote dialogue, share knowledge, and develop policies to eliminate poverty and enable a dynamic private sector. It aimed to strengthen Djibouti s capacity to define, through a concerted open dialogue, a path to sustainable development, and ensure that growth translates into poverty reduction, jobs, and economic opportunities for all. The experiences of Cape Verde, Mauritius, and Dubai, also demonstrate that the small size of the Djiboutian market, along with the high cost of electricity, do not constitute binding constraints to economic development. It is critical that serious consideration be given to the recommendations made during the roundtables. To this end, the implementation of sector-specific five-year plans by the Government of Djibouti should include, to the extent possible, consultations between private and public actors and civil society.